Hepatitis C virus elimination in Indonesia: Epidemiological, cost and cost‐effectiveness modelling to advance advocacy and strategic planning. (29th October 2019) - Trickey, Adam; Hiebert, Lindsey; Perfect, Chase; Thomas, Caroline; El Kaim, Jean Luc; Vickerman, Peter; Schȕtte, Carl; Hecht, Robert
Abstract: Backgrounds & Aims: In Indonesia 1.9 million people are chronically infected with hepatitis C virus (HCV), but a national strategic plan for elimination has not yet been developed, despite the availability of low‐cost treatments which could save many lives. We used epidemiological and cost modelling to estimate targets and resource requirements of a national elimination program and explore the potential impact and cost‐effectiveness. Methods: To model the HCV epidemic, we used a dynamic model, parameterised with Indonesia‐specific data, accounting for disease progression, injecting drug use and demographics. Future scale‐up scenarios were designed for 2018‐2050 to capture possible policy choices. Costs of an initial 5‐year national strategy and of long‐term elimination were estimated for the most feasible scenario, as agreed with government and local partners. Cost savings from reduced drug and diagnostics prices were also estimated. The cost‐effectiveness of baseline predictions and those with drug price reductions were compared to the no treatment scenario. Results: Elimination by 2045, considered the most feasible path to scale‐up, would prevent 739 000 new infections and avert 158 000 HCV‐related deaths. The costs would be 5.6 billion (USD) using baseline prices but could fall to 2.7 billion if price reductions for HCV drugs and diagnostics are secured. With these price reductions, the incremental cost‐effectiveness ratio for a 2045 elimination program would be cost‐effective at 300 (USD) per year of life saved vs the no treatment scenario. Conclusions: This study has underpinned advocacy efforts to secure Indonesian government commitment to HCV elimination, and provides further inputs for HCV strategic planning efforts.